A influência da mímese na hermenêutica simbólica de Paul Ricoeur - Belo, Eliezer (2015)
This work performs an approach about hermeneutics symbol in Paul Ricoeur from the perspective of mimesis. To understand the importance of mimesis in hermeneutics of Ricoeur was mythologically it was decided to develop the study to present the stages of development of thought. The first study was based on the knowledge of the philosophy of the will. This first part intended to show Ricoeur entry in the symbol field. In the following reflections and evolution of thought. Another part complements this first study and tried to assess the graft hermeneutic phenomenology. The proposition of this second part was to justify the existence of a symbol of hermeneutics, considering the symbol as a possible starting point for resolving the conflict of interpretations. Another study complemented this work is developed in three stages. First concentrated in the field of hermeneutics from developing a myth and symbol description, with the intention of presenting the range of dimensions of the symbols. Then was taken into account the evolution of speech to reach the write state. In that same set, the myth and the symbol are analyzed from the aspect of semantic mediation that is between them. Subsequent to this second part held a reflection on the time in Augustine and Aristotle, considering the dimensions of the experience of time. The study which end the study was conducted in three stages. The first and the second are devoted to the relationship between mimesis and muthos, and mediation between mimesis I and III by mimesis II. The second focused on the reader, and the figure of the world’s mimesis consolidation and setting, via reflection on the reference. The closure was left with the task of carrying out an assessment of the symbol of hermeneutics, considering aspects of mimesis, the action imitated in the narration, the time of the work and the reader's worlds and work as configuration elements.